Implementation of “Ngerti, Ngrasa, Nglakoni” in The Leadership of Sono Hamlet Youth Organization - Jamaluddin, Akmal; Nurjana, Anisa; Noperian, Jogi; Dewi, Esta Lestariana; Putrisia, Ezdwima; Kusumawardhani, Ratih (PT Inovasi Pratama Internasional, 2024)
The main objective of this program is to provide provision and guidance that operates in the social and environmental fields with the main focus on the development of young people. Community Service was carried out on October 15 2024 in Sono Hamlet, Kretek District, Bantul Regency. This Community Service ran smoothly and was attended by 11 young people out of 15 invited people. The material presented is related to the concept of student gardens, namely Tri Nga